Fantasmas del pasado frente a soldados del presente: retórica e historiografía en el nuevo enfoque cultural de la historia militar grecolatina - Iglesias Zoido, Juan Carlos (Talia dixit, 2007)
The purpose of this paper is to analyze in depth some of the implications that have the recent publication of the book of J. E.Lendon (Soldados y fantasmas. Historia de las guerras en Grecia y Roma, Barcelona: Ariel, 2006) for the study of the relations between rhetoricand historiography in the graeco-roman Antiquity.